2021
DOI: 10.33069/cim.2021.0002
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia among Active Patients with COVID-19: A Cross-Sectional Study

Abstract: Coronavirus disease (COVID-19), a highly contagious virus, first observed in the Chinese city of Wuhan in late December of 2019, has spread across the world resulting in significant morbidity and mortality [1]. The nature of the pandemic with respect to lack of any specific treatment or vaccine along with strict control measures has resulted in significant psychological symptoms among general population [2]. Moreover, patients with COV-ID-19 infection also been shown to be vulnerable to a various psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One of the reason for this higher prevalence could be that many studies included frontline hospital staff who are actively involved in COV-ID-19 management, and significantly higher rate of insomnia was reported among them. Moreover, the relatively lower prevalence of sleep disorder in our study also can be due to difference in scales used across studies [9]. It has been found that studies using the Pittsburgh Sleep Quality Index (PSQI) scale found significantly higher rate insomnia among the study participants as the questions in the PSQI assess wide range of sleep-related issues [9].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…One of the reason for this higher prevalence could be that many studies included frontline hospital staff who are actively involved in COV-ID-19 management, and significantly higher rate of insomnia was reported among them. Moreover, the relatively lower prevalence of sleep disorder in our study also can be due to difference in scales used across studies [9]. It has been found that studies using the Pittsburgh Sleep Quality Index (PSQI) scale found significantly higher rate insomnia among the study participants as the questions in the PSQI assess wide range of sleep-related issues [9].…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, the relatively lower prevalence of sleep disorder in our study also can be due to difference in scales used across studies [9]. It has been found that studies using the Pittsburgh Sleep Quality Index (PSQI) scale found significantly higher rate insomnia among the study participants as the questions in the PSQI assess wide range of sleep-related issues [9].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations